Violence in a family is a social problem (The Journal of Psychology and Sociology, 2012)
Allocation of domestic violence as a separate social problem is a priority step towards its resolution. Each particular violence – an independent problem, which has speciﬁ c features. In this way, there are number of obstacles: the lack of clear deﬁ nitions and theoretical framework, the lack of comprehensive information about the extent and causes of the use of force in the family, as well as the lack of legal framework. In order to overcome domestic violence, some punitive measures are not enough; we need serious work in the ﬁ eld of prevention and education.
Keywords: violence; social problem; social wоrk; crime; lаtency.